Age at Menarche and Menopause, Reproductive Lifespan, and Risk of Cardiovascular Events Among Chinese Postmenopausal Women: Results From a Large National Representative Cohort Study - Chen, Lu; Hu, Zhen; Wang, Xin; Song, Yuxin; Chen, Zuo; Zhang, Linfeng; Zheng, Congyi; Vallis, Jillian; Zhou, Haoqi; Cao, Xue; Tian, Yixin; Cai, Jiayin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The association between age at menarche and menopause, reproductive lifespan, and CVD risk amongst postmenopausal women is contradictory. Methods: A total of 7,811 Chinese postmenopausal women with a mean age of 63.9 years were enrolled at baseline from 2012 to 2015 and followed up during 2018-2019. A standardized questionnaire was used to collect relevant information by well-trained interviewers. Physical examination of the participants was performed by trained medical staff. CVD events were observed during follow-up. Cox proportional hazards models were used to estimate hazard ratios between reproductive characteristics and CVD events. Results: Age at menarche was positively associated with CVD events (HR, 1.128; 95%CI, 1.044–1.218). There was a negative association between age at menopause and CVD risk in postmenopausal women with no family history of CVD (HR, 0.952; 95%CI, 0.909–0.996). Reproductive lifespan was negatively associated with CVD events (HR, 0.951; 95%CI, 0.916–0.986). The CVD risk increased by 12.8% for every 1-year increase in age at menarche. The CVD risk reduced by 4.8% for every 1-year increase in age at menopause in women with no family history of CVD. The CVD risk reduced by 4.9% for every 1-year increase in reproductive lifespan. Conclusions: Based on the large prospective study with a nationally representative sample, Chinese postmenopausal women with late age at menarche and shorter reproductive lifespan have higher risk of CVD events. Keywords: Age at menarche; Age at menopause; Reproductive lifespan, Cardiovascular events; Postmenopausal women